An empirical study on creating software product value in India – an analytic hierarchy process approach. (1st January 2015) - Latha, T. Jessie; Suganthi, L.
India is growing strongly in the software industry and has a dynamic global market in software development. In today's competitive market it is necessary for the software companies to maximise the creation of software product value to remain a success in the market. The value of a software product is largely derived through the fulfilment of requirements. Therefore, it is necessary to carefully select the requirements to include in a specific software release. This paper presents an empirical study to understand how the value is created by finding the importance of different decision-making criteria and the perspectives that motivates them. The study is carried out among multinational software companies operating in India. The analytic hierarchy process is used to find the relative importance of the 13 criteria and to prioritise them by considering what creates business value in a software product. The results depict that for any product to be accepted in the market or by the potential customers business perspective is vital.